A Man Called Brian - Shoolizadeh, Mahmoud (United Kingdom, 2005)
Verzio FF submission The film introduces 55 year-old Briton called Brian Haw who has staged a 24-hour sit-in opposite the Houses of Parliament in London for over five years in protest against the invasion of US and British military forces of Iraq and Afghanistan.